Maternal death at Leratong Regional Hospital: a six-year retrospective review, South Africa - Motau, Tumelo Ngaka (University of the Witwatersrand, Johannesburg, 2021)
Background: The aim of the study was to systematically examine the main causes of maternal deaths and contributing factors at Leratong Regional Hospital in order to recommend strategies that can assist in reducing maternal mortality at this level of healthcare. Objectives: The objectives of the study were to: determine the institutional maternal mortality rate at Leratong Regional Hospital between 2012 to 2017, compare the trend (year on year) in the iMMR over the study period, describe the profile of women who died during the period under study, describe the clinical and surgical management of the women who died, and to determine the leading causes of maternal deaths, contributing factors and avoidable factors. Methods: A hospital based retrospective study based on patient clinical records at Leratong hospital. It included all the maternal deaths that occurred at Leratong Regional Hospital during the six-year study period (2012-2017). Results: There was a total of 78 maternal deaths with 32441 live births giving the MMR of 240 per 100 000 live births. However only 74 files could be analysed. The results showed that there was a rise in the maternal mortality rate over a six years period. The majority (70, 94.5%) of the women who died were African, aged between 20-35 years (56, 76%), multigravida (54,73%) with a parity of three or more (23, 31%). Obstetric haemorrhage was the leading cause of maternal death particularly postpartum haemorrhage (11.14%) followed by non-pregnancy related infections, sepsis and eclampsia. Conclusion: Maternal mortality has decreased according to recent confidential enquiry into maternal death in South Africa (2017-2019) However our study did not demonstrate a decline but rather an increase in the maternal mortality rate at Leratong. It showed that most of the maternal deaths were avoidable and the need for urgent interventions in terms of education, improving access to health care facilities, intensifying health care worker skills training and better transport systems between health care facilities is important.
A research report submitted in partial fulfilment for the degree of Masters in Medicine (Obstetrics & Gynaecology), to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021.
Keywords: Maternal deaths; Leratong Regional Hospital; Maternal mortality; Clinical and surgical management of the women; Obstetric haemorrhage; Postpartum haemorrhage; South Africa; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education